2017
DOI: 10.1152/ajplung.00415.2016
|View full text |Cite
|
Sign up to set email alerts
|

Active vs. sedentary lifestyle from weaning to adulthood and susceptibility to ozone in rats

Abstract: The prevalence of a sedentary (SED) life style combined with calorically rich diets has spurred the rise in childhood obesity, which, in turn, translates to adverse health effects in adulthood. Obesity and lack of active (ACT) lifestyle may increase susceptibility to air pollutants. We housed 22-day-old female Long-Evans rats in a cage without (SED) or with a running wheel (ACT). After 10 wk the rats ran 310 ± 16.3 km. Responses of SED and ACT rats to whole-body O (0, 0.25, 0.5, or 1.0 ppm; 5 h/day for 2 days)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…But the persistent inflammation in respiratory system frequently leads to some adverse diseases such as asthma, COPD, and pulmonary fibrosis. In addition, neutrophils can synergize with lymphocytes and other granulocytes, such as Th2/Th17 and eosinophils, to participate in not only innate but also adaptive immune process and promote airway inflammation [22, 23]. The interaction between neutrophils and other immune cells, endogenous composition, and foreign matter is very complex and being clarified thoroughly.…”
Section: Introductionmentioning
confidence: 99%
“…But the persistent inflammation in respiratory system frequently leads to some adverse diseases such as asthma, COPD, and pulmonary fibrosis. In addition, neutrophils can synergize with lymphocytes and other granulocytes, such as Th2/Th17 and eosinophils, to participate in not only innate but also adaptive immune process and promote airway inflammation [22, 23]. The interaction between neutrophils and other immune cells, endogenous composition, and foreign matter is very complex and being clarified thoroughly.…”
Section: Introductionmentioning
confidence: 99%
“…In either case, the organism’s physiological endpoints (i.e., behavioral, pulmonary, cardiac, metabolism, etc.) are the main focus [18,19]. There are few, if any, studies related to the possible interaction between diet and O 3 , especially on brain neurochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…In women, sedentary behavior can lead to premature menopause [8]. It can also lead to obesity in children, with negative carry-over effects on their adult health [9]. Studies have found that older adults who exercise regularly will have healthier breathing systems than those who display more sedentary behavior [10].…”
Section: Motivationmentioning
confidence: 99%